Humanistic And Sophistic Psychology Coherence In Improving Emotional Well-Beeing In Modern Era - Maulana Asrori (IJIP : Indonesian Journal of Islamic Psychology, 2023)
The coherence of and humanistic psychology and Sufistic psychology in their implementation improves psychology in the modern era which is very influential and dominates. In the era of modernization, it has positive and negative influences on human life. On the one hand, the development of the times provides benefits in assisting human activities in all dimensions of life, but on the other hand, it can create new problems that cause damage and decrease in human psyche. This research uses information retrieval techniques from phenomenological studies that exist in the community, with the type of qualitative research using descriptive methods. Collecting data using interview methods, and observation. While data reduction is used as data analysis. This research aims to describe or explain systematically and clearly about the relationship between psychological theory and events that occur in society in an effort to improve psychology in modern times. The results of this research found that there is coherence and connection between and humanistic psychology and Sufistic psychology in their efforts to improve and improve psychology in today's modern era.